2013
DOI: 10.2215/cjn.02350213
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cholesterol Levels with Mortality and Cardiovascular Events among Patients with CKD and Different Amounts of Proteinuria

Abstract: SummaryBackground and objectives Malnutrition and/or inflammation may modify the risk relationship of total cholesterol with cardiovascular disease in CKD patients. However, it is unclear whether the relationship of total cholesterol with cardiovascular events and mortality varies by proteinuria. Results During a median 2.8-year follow-up, there were 471 (14.3%) deaths and 545 (16.5%) cardiovascular events. In an adjusted Cox model, the two highest quartiles of total cholesterol (hazard ratio, 1.90; 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that TC level was associated with a higher risk of mortality in patients with chronic renal failure [ 20 21 ]. Chen et al [ 22 ] in a more recent large-scale study among 3,303 patients with chronic kidney disease stages 3 to 5, observed that the association between TC and mortality is different among patients with different levels of proteinuria. Though Pearson correlation analysis did not demonstrate any significant correlation between HDL-C and eGFR, HDL-C was identified to be associated with declining eGFR in our study, on regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TC level was associated with a higher risk of mortality in patients with chronic renal failure [ 20 21 ]. Chen et al [ 22 ] in a more recent large-scale study among 3,303 patients with chronic kidney disease stages 3 to 5, observed that the association between TC and mortality is different among patients with different levels of proteinuria. Though Pearson correlation analysis did not demonstrate any significant correlation between HDL-C and eGFR, HDL-C was identified to be associated with declining eGFR in our study, on regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline proteinuria is known to be associated with the risk of CKD progression in both nondiabetic [ 28 ] and diabetic [ 29 , 30 ] patients. Recently Chen et al also reported that various degrees of proteinuria may have different impact on cardiovascular events and all-cause mortality [ 31 ]. However, the interrelationship between proteinuria and vascular calcification remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…All clinically relevant covariates were selected according to our previous publications and literature and continuous variables with a skewed distribution were log transformed to attain normal distribution. Adjusted covariates included age, gender, hypertension, CVD, diabetes mellitus, current smoking status, MAP, eGFR, log-transformed Upcr, albumin, hemoglobin, HbA1C, log-transformed total cholesterol, log-transformed CRP, and phosphorus [ 23 25 ]. Cox survival analyses with pre-specified subgroups were also performed by adding appropriate cross-product interaction terms including age, gender, CVD, CKD stages, Upcr, hemoglobin, albumin, and CRP.…”
Section: Methodsmentioning
confidence: 99%